Pendekatan Risiko dalam Perencanaan dan Pengawasan Organisasi Pendidikan - Lida Yati; Irsyad, Irsyad; Tia Ayu Ningrum (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study examines the risk approach in planning and monitoring educational organizations. The purpose of this study is to determine the risk approach in educational organizations as a strategic effort to improve the affectiveness as a strategic effort to improve the effectiveness, afficiency and accountability of educational implementation. Risk is the opportunity for adverse events to accur, which is caused by uncertainty. The risk approach includes various factors than can affect the smoothness of daily activity ptocesses. Risk management strategies help organizations anticipate potential problems and implement appropriate preventive measures to minimize negative impacts on overall company productivity and performance. In the context of planning, the risk opproach helps educational institutions explore potential threats and develop mitigation steps before risks impact organizational performance, while in supervision, this approach functions as an early detection and evaluation system for internal control so that all operational activities run according to the standars and objectives of the institution. This research method utilizes a literature review based on articles, journals, and books. These results indicate that the risk opproach has an important role in increasing the affectiveness of planning and monitoring of educational organizations.